A confiança e a satisfação como mediadoras no varejo multicanal - Groh, Cesar Augusto (2009)
This study investigated the rules of the satisfaction and trust as mediating variables of the relationships between attitudes, future intentions and loyalty of consumers on multichannel retailing. Based upon the studies of Garbarino and Johnson (1999), which postulates that for relational consumers trust is the mediating variable between the attitudes and the future intentions whereas, for transactional consumers, the satisfaction is the mediating variable. Given to the characteristics of both traditional and electronic commerce retailing, the mediating variable for each channel would be, respectively, the satisfaction and trust. Therefore a theoretical model is proposed and in sequence evaluated by Structural Equations Modeling. The results show that trust has a preponderant role in the future intentions involving companies who act multichannel. Also the role of these variables in the determination of loyalty was investigated. The conclusion suggests that trust is more significant for the sedimentation of loyalty in the electronic retailing than in the conventional one.